2019
DOI: 10.3892/ol.2019.10751
|View full text |Cite
|
Sign up to set email alerts
|

Prospective applications of microRNAs in oral cancer: A review (Review)

Abstract: MicroRNAs (miRNAs) are non-coding RNA molecules that are generally encoded by endogenous genes and exert suppressive effects on post-transcriptional regulation of their target genes by translation repression or degradation of mRNA. This subsequently mediates activation or blocking of downstream signaling pathways associated with oral malignancies. Aberrant levels of certain miRNAs have been identified in cell experiments, clinical carcinomatous specimens, saliva, serum or plasma samples of patients with oral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 125 publications
(120 reference statements)
0
24
0
Order By: Relevance
“…Primarily, two classes of miRNAs, oncomiRs and tumor suppressor miRs (TS-miRs), are observed that regulate the expression of oncogenes and tumor suppressor genes, respectively [ 30 ]. Accumulating evidence has shown insight into the functional role of the deregulated miRNAs in controlling the expression of their target mRNAs, leading to regulation of signaling pathways involved in oral cancer [ 31 , 32 , 33 ]. A total of 2300 true human mature miRNAs have been identified, but their action on target mRNAs is challenging to characterize due to their multi-target inherent nature.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, two classes of miRNAs, oncomiRs and tumor suppressor miRs (TS-miRs), are observed that regulate the expression of oncogenes and tumor suppressor genes, respectively [ 30 ]. Accumulating evidence has shown insight into the functional role of the deregulated miRNAs in controlling the expression of their target mRNAs, leading to regulation of signaling pathways involved in oral cancer [ 31 , 32 , 33 ]. A total of 2300 true human mature miRNAs have been identified, but their action on target mRNAs is challenging to characterize due to their multi-target inherent nature.…”
Section: Introductionmentioning
confidence: 99%
“…These noncoding RNAs, generally composed of 18–22 nucleotides, can suppress the expression of corresponding genes by targeting the 3′-untranslated regions of mRNA and subsequently regulate the malignant behaviors of cancer cells. In oral cancer, several oncogenic or tumor-suppressive miRNAs have been reported, and investigations on how these small RNAs regulate lymph node metastasis have been noteworthy [ 86 , 87 , 88 ]. To explore the biological function of miRNA in regulating lymph node metastasis in oral cancer, we analyzed the gene expression profiles of a Taiwanese cohort that were established using genomic DNA and mRNA from 40 tumor tissues and matched oral mucosa [ 89 , 90 , 91 , 92 ].…”
Section: Perspectives On Molecular Tumorigenesismentioning
confidence: 99%
“…Numerous miRNAs have been shown to be significantly expressed in various cancers, including OSCC, acting as tumor suppressors and/or oncogenes. However, there is limited information about lncRNAs in OSCC and their function as sponges for expressed miRNAs ( 7 , 9 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the expression accuracy, we chose two miRNAs for further analysis, i.e. , miR-34a and miR-145 , and three lncRNAs, ROR , SNGH1 , and AB209630 ( 7 , 10 , 12 , 13 ), to reveal whether their expression supports the dynamics of the observed patterns of NANOG expression in OSCC cancerogenesis.…”
Section: Introductionmentioning
confidence: 99%